2013
DOI: 10.1109/jqe.2013.2260725
|View full text |Cite
|
Sign up to set email alerts
|

Mode Competition Induced by Optical Feedback in Two-Color Quantum Dot Lasers

Abstract: We investigate theoretically the impact of optical feedback on quantum dot two-color laser dynamics when emitting from both the excited and the ground states. Detailed analysis of the laser dynamics is provided by numerical integrations and continuation techniques, as well as by analytical methods. As the feedback strength is increased the quantum dot laser undergoes a sequence of bifurcations involving steady-states, external cavity modes, self-pulsations and chaos. Furthermore, we report on two interesting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…7(b) the rate increases to 4.9e-3 mW/degree. For higher I b lower θ p is needed for PS as in line with theoretically predicted data reported in [26]. The results demonstrated that I b can affect the PS dynamic of VCSEL, where a smaller θ p is required to implement PS when the bias current increase.…”
Section: Effects Of Modulation-depthsupporting
confidence: 87%
“…7(b) the rate increases to 4.9e-3 mW/degree. For higher I b lower θ p is needed for PS as in line with theoretically predicted data reported in [26]. The results demonstrated that I b can affect the PS dynamic of VCSEL, where a smaller θ p is required to implement PS when the bias current increase.…”
Section: Effects Of Modulation-depthsupporting
confidence: 87%
“…We explore the time dependent light emission dynamics of the bimodal micropillar lasers and provide the first experimental evidence of statistical switching reported for these kind of microscale devices. We clearly show that the nonlinear dynamics of these nanostructured devices can be described (qualitatively and quantitatively) with relatively simple rate equations adapted from the well known two-mode ring laser [12][13][14] and VCSEL [6,7,[15][16][17] models. Fully quantum mechanical theories that derive the equations of motion for photons and correlation expectation values [18,19] have their strength in describing single photon emitters [20] and have also been used to describe the micropillar lasers and their bimodal properties [21].…”
Section: Introductionmentioning
confidence: 89%
“…the reduction of effective optical losses of the weak mode by 2.5%, thus reducing the required inversion of the QDs to maintain lasing and reducing the available gain for the strong modes, as known from two-mode lasers in other setups [62][63][64]. In Fig.…”
Section: Intensity Auto-and Cross-correlationsmentioning
confidence: 99%